DNA glycosylase NEIL2 functions in multiple cellular processes. (September 2021) - Sarker, Altaf H.; Cooper, Priscilla K.; Hazra, Tapas K.
Abstract: Cell survival largely depends on the faithful maintenance of genetic material since genomic DNA is constantly exposed to genotoxicants from both endogenous and exogenous sources. The evolutionarily conserved base excision repair (BER) pathway is critical for maintaining genome integrity by eliminating highly abundant and potentially mutagenic oxidized DNA base lesions. BER is a multistep process, which is initiated with recognition and excision of the DNA base lesion by a DNA glycosylase, followed by DNA end processing, gap filling and finally sealing of the nick. Besides genome maintenance by global BER, DNA glycosylases have been found to play additional roles, including preferential repair of oxidized lesions from transcribed genes, modulation of the immune response, participation in active DNA demethylation and maintenance of the mitochondrial genome. Central to these functions is the DNA glycosylase NEIL2. Its loss results in increased accumulation of oxidized base lesions in the transcribed genome, triggers an immune response and causes early neurodevelopmental defects, thus emphasizing the multitasking capabilities of this repair protein. Here we review the specialized functions of NEIL2 and discuss the consequences of its absence both in vitro and in vivo .